Genetic Divergence Study in Grewia Optiva through Quantitative and Molecular Markers - Bhagta, Shikha; Thakur, Poonam; Sharma, Dushyant (International Journal of Economic Plants, 2021)
Diversity analysis amongst 10 different families of Grewia optiva was carried out by using RAPD (random amplified polymorphic DNA) and ISSR (inter simple sequence repeats) marker. Grewia optiva families were raised by seed collected from various districts of Himachal Pradesh (India) and selected based on morphological parameters. Using 15 RAPD and 20 ISSR primers and 9 RAPD and 12 ISSR primers show amplification respectively. Nine RAPD primers showed 68.96% polymorphism and 12 ISSR primers showed 71.25% polymorphism. Similarity matrices and Dendrograms were generated using SAHN module of NTSYSpc ver.2.02h. Jaccard’s similarity matrix revealed maximum similarity coefficient 0.88 between ‘SO-7’ and ‘SO-3’ with RAPD primers. For ISSRs, coefficient values ranged from 0.52 to 0.80. Dendrograms also revealed to larger extent similar results and maximum similarity found among the 10 families of Grewia optiva collections was 88% between ‘SO-7’ and ‘SO-3’with RAPD primers and 80% between ‘SH-7’ and ‘SO-4’ with ISSRs. RAPD and ISSR were found effective in revealing polymorphisms among 10 different genotypes of Grewia optiva. UPGMA based dendrograms of both RAPD and ISSR confirmed the placement of different genotypes into different clusters and sub clusters as per geographic distribution and genetic constitution. Family SH-7 came as outliner as revealed by both RAPD and ISSR study.